2002
DOI: 10.1046/j.1365-2869.2002.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of sleep and sleep EEG after hemispheric stroke

Abstract: SUMMARY The evolution of subjective sleep and sleep electroencephalogram (EEG) after hemispheric stroke have been rarely studied and the relationship of sleep variables to stroke outcome is essentially unknown. We studied 27 patients with first hemispheric ischaemic stroke and no sleep apnoea in the acute (1–8 days), subacute (9–35 days), and chronic phase (5–24 months) after stroke. Clinical assessment included estimated sleep time per 24 h (EST) and Epworth sleepiness score (ESS) before stroke, as well as ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 28 publications
(31 reference statements)
3
85
1
7
Order By: Relevance
“…We found that nocturnal sleep quality was generally poorer and daytime sleepiness was higher in patients with a first-time stroke between one and 15 years ago. This supports the assumption that sleep problems, frequently observed in the acute phase post stroke, may indeed evolve into a chronic problem in some individuals [10,12,13]. These results should be interpreted with caution due to the preliminary nature of the study.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…We found that nocturnal sleep quality was generally poorer and daytime sleepiness was higher in patients with a first-time stroke between one and 15 years ago. This supports the assumption that sleep problems, frequently observed in the acute phase post stroke, may indeed evolve into a chronic problem in some individuals [10,12,13]. These results should be interpreted with caution due to the preliminary nature of the study.…”
Section: Introductionsupporting
confidence: 84%
“…It also revealed that it is unclear to what extent the sleep problems reported in the early phase after a stroke are transient. Some authors suggest that post-stroke sleep disturbances actually persist and become a chronic condition [10][11][12][13], but the evidence-base for this claim is poor and the prognosis beyond one-year post injury is not well understood. This is partly due to the use of heterogeneous study groups comprised of patients in various stages of recovery and with various levels of functional ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One prevailing theory with strong supportive evidence is that sleep serves a restorative function for the brain and body. Chronic insufficient sleep is a risk factor for a variety of psychological [9][10][11][12][13], neurological [14][15][16][17][18][19] and neurodegenerative pathologies [16], as well as cardiovascular and metabolic dysfunctions [20][21][22][23][24]. More recent findings from clinical studies reveal that women suffering from sleep disturbances and insufficient sleep are at greater risk compared with men for mood disorders such as depression [25], as well as metabolic [26] and cardiovascular dysfunction [23,[27][28][29].…”
Section: Overview Of Sleepmentioning
confidence: 99%
“…The contrasting role is undoubtedly played by the amount of electroencephalographic literature regarding that kind of examination in humans. Most of the technical aspects, such as electrodes localization, research apparatus used and ranges of particular brain waves are widely known and successfully used in practice (Lesser et al 1985, Butler 1987, Homan et al 1987, Rosenblatt et al 1999, Vock et al 2002, Danko et al 2002, Armitage et al 2003, Velis 2005. Despite the many different opinions of researchers, it is certain that the electroencephalographic diagnostic is regarded highly among neurophysiological examinations and may be successfully used, not only in humans but in animals as well.…”
Section: Electroencephalography Application In the Research On The Cementioning
confidence: 99%